Нейросетевая модель факторного анализа - Бодянский, Е. В.; Запорожец, О. В.; Путятина, Т. В.; Рагулина, О. Е. (ХТУРЭ, 1999)
Наиболее-эффективным для решения проблемы сжатия больших массивов данных является метод главных компонент факторного анализа. При поступлении данных в реальном масштабе времени целесообразно использование идеи рекурсивного вычисления главных компонент. Principal compunenl method of factorial analysis is most effective for data compression problem solution II data are collected in real lime it is advisable to use an idea of recursive calculation of the main components and liebb-Senger extended algorithm, l ire algonthn: is implemented as artificial neuron network consisting ol Oja's neurons
Keywords: сжатие больших массивов данных; факторный анализ